+0

# if x^2-2011x+1=0 is true,then waht is the value of x-2010x+2011/(x^2+1)?

+8
379
14
+238

if x^2-2011x+1=0 is true,then waht is the value of x-2010x+2011/(x^2+1)?

quinn  Sep 25, 2014

#9
+81032
+13

x2 = 2011x - 1  →  x2 + 1 = 2011x

So

x^2-2010x+【2011/(x^2+1)] =

[2011x - 1 ] - 2010x + 2011/(2011x) =

x - 1 + 1/x =

[x2 - 1x + 1] / x =

[x2 + 1 - x ] /x =

[2011x - x] / x =

2010x / x =

2010      (with the restriction that x ≠ 0)

CPhill  Sep 25, 2014
Sort:

#1
+91469
+8

$$\\If\;\; x^2-2011x+1=0  is true, then what is the value of \\\\ x-2010x+\frac{2011}{(x^2+1)}\;\;?\\\\ first\\ x^2-2011x+1=0\\ x^2+1=2011x\\\\ now\\\\\ x-2010x+\frac{2011}{(x^2+1)}\\\\ =x-2010x+\frac{2011}{(2011x)}\\\\ =x-2010x+\frac{1}{x}\\\\ =-2009x+\frac{1}{x}\\\\$$

Maybe you needed more brackets in your question?  I think that you probably did.

Melody  Sep 25, 2014
#2
+238
+8

oh. i am sorry the second equation should be x^2-2010x+2011/(x^2+1)

quinn  Sep 25, 2014
#3
+91469
+8

Maybe you really mean this ??

(x^2-2010x+2011) /(x^2+1)

Is that right?

Melody  Sep 25, 2014
#4
+238
+8

x^2-2010x+【2011/(x^2+1)]

quinn  Sep 25, 2014
#5
+91469
+8

$$\\If\;\; x^2-2011x+1=0  is true, then what is the value of \\\\ x-2010x+\frac{2011}{(x^2+1)}\;\;?\\\\ first\\ x^2-2011x+1=0\\ x^2+1=2011x\\\\ now\\\\\ x^2-2010x+\frac{2011}{(x^2+1)}\\\\ =x^2-2010x+\frac{2011}{(2011x)}\\\\ =x^2-2010x+\frac{1}{x}\\\\ =(x^2+1)-1-2010x+\frac{1}{x}\\\\ =2011x-1-2010x+\frac{1}{x}\\\\ =x-1+\frac{1}{x}\\\\$$

$$\\=\frac{x^2-x+1}{x}\\\\ =\frac{1011x-x}{x}\\\\ =\frac{1010x}{x}\\\\ =1010$$

I think I might have stuffed up somewhere.  Plus I have a reputation for doing things the LONG way.

I'm going to look over it some more.

Melody  Sep 25, 2014
#6
+91469
+3

No I think i am happy enough with that answer.

Melody  Sep 25, 2014
#7
+8256
0

Melody. Lol! That was so funny.

DragonSlayer554  Sep 25, 2014
#8
+91469
0

I am glad that you find me entertaining Dragon.

Melody  Sep 25, 2014
#9
+81032
+13

x2 = 2011x - 1  →  x2 + 1 = 2011x

So

x^2-2010x+【2011/(x^2+1)] =

[2011x - 1 ] - 2010x + 2011/(2011x) =

x - 1 + 1/x =

[x2 - 1x + 1] / x =

[x2 + 1 - x ] /x =

[2011x - x] / x =

2010x / x =

2010      (with the restriction that x ≠ 0)

CPhill  Sep 25, 2014
#10
+91469
+8

I thought about the restriction Chris but I didn't put it there because the first statement would not be true if x=0.

But like always - yours is shorter.

I started mine from the previous result where the question was wrong.

That is my excuse and I am sticking with it!  LOL

Melody  Sep 25, 2014
#11
+81032
+8

I'll put it down to your "left-handedness".............LOL!!!!!

CPhill  Sep 25, 2014
#12
+238
+8

(x^2-2011x+1)/x=0/x

x-2011+1/x=0

x+1/x=2011

x-1+1/x=2011-1=2010

Good job.Is it funny or not to do problem like this?if yes, i will put a problem everyday to the forum

quinn  Sep 25, 2014
#13
+81032
+8

It IS fun, quinn.......just don't make them too difficult......otherwise, it makes us look bad........

P.S  ....I even had to "cheat" off Melody a bit to get that problem correct!!!!  (Shhh!!!...don't tell her)

CPhill  Sep 25, 2014
#14
+91469
+8

Yes I had fun with this problem quinn.

But it is better if you get the question right in the first place.  I liked the Extra brackets that you put in second time round, then we know we have not misinterpreted.

I have included this problem in the next "End of Day Wrap" that i  write.  I invite you to read my wrap.  I write one most nights.

Here is the address of yesterday's one.  They are kept in with the sticky topics.  :)

(I don't usually include that many questions but I had not written one for a few days)

We really DID LIKE this question Quinn, you are welcome here any time

Melody  Sep 25, 2014

### 1 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details